Палеоекологія околиць Глинського археологічного комплексу ХІІІ-XIV ст. - Пуголовок, Ю.О.; Горбаненко, С.А.; Сергєєва, М.С.; Яніш, Є.Ю. (Археологія, 2015)
До наукового обігу вводиться блок нових даних, що стосується різнобічних палеоекологічних аспектів, які було отримано завдяки застосуванню методів природничих досліджень до матеріалів з Глинського археологічного комплексу XIII—XIV ст. Блок складається з чотирьох окремих досліджень: палеоетноботанічних, археозоологічних, археоіхтіологічних і дендрологічних. Ретельний аналіз цього блоку та зіставлення отриманих незалежно природничих даних, а також загальних палеоприродних досліджень надало підґрунтя для комплексного вивчення навколишнього середовища Глинського у давнину. Presented to the scientific circles here is a new data bloc concerning various palaeoecological aspects which was obtained with help of natural science methods in the research of materials from Hlynske archaeological assemblage of the 13th and 14th centuries. The bloc consists of four independent investigations: palaeoethnobotanic, archaeozoological, archaeoichthyological, and dendrological ones. The materials for analysis of three of the four directions (except the archaeozoological one) were obtained thanks to the widening of traditional archaeological methods of the study owing to the flotation and panning out application. Careful analysis of the available information bloc and the comparison of independently obtained natural scientific data, as well as of general palaeo natural research formed the base for a comprehensive analysis of the environment in ancient Hlynske. The materials obtained testify that the usage of thorough research methods is perspective, and owing to these methods the base for the comprehensive interdisciplinary approach to the treatment of various organic remains is accumulated. Such approach allows widening significantly the sources for study the economy of ancient habitants in Hlynske micro region, as well as detailing the palaeoecological aspects of its life. В научный оборот вводится блок новых данных, касающийся разносторонних палеоэкологических аспектов, который был получен методами естественнонаучных исследований материалов Глинского археологического комплекса XIII—XIV вв. Блок состоит из четырех независимых исследований: палеоэтноботанических, археозоологических, археоихтиологических и дендрологических. Материалы для анализа трех из четырех направлений (кроме археозоологических) получены благодаря расширению традиционных археологических методов исследований за счет применения флотации и промывки. Тщательный анализ полученного блока информации и сопоставление полученных независимо естественнонаучных данных, а также общих палеоприродных исследований составил основу для комплексного анализа окружающей среды Глинского в древности. Полученные материалы свидетельствуют о перспективности использования тщательных методов исследований, благодаря которым накапливается основа для комплексного междисциплинарного подхода к обработке различных органических остатков. Такой подход позволяет существенно расширить источники к изучению хозяйства древнего населения Глинского микрорегиона, а также детализировать палеоэкологические аспекты его жизнедеятельности.